Strategic Study on The Business Development of Regional Owned Enterprises in Tanjungpinang City - S. Suryadi; F. Fatahurazak; Oksep Adhayanto; Bismar Arianto (Manunggal Halim Jaya, 2022)
PT. Tanjungpinang Makmur Bersama (PT. TMB) is a Regional Owned Company in Tanjungpinang City; the company's current activities are: Running a business in the field of regional asset monitoring services in the form of leasing: stores and places of business by renting out to tenants as small entrepreneurs and traders of essential goods for the people of Tanjung City. This study aims to discover and explore the possibility of how BUMD can develop economic resources. This research focuses on identifying internal and external factors for what happened to PT. Tanjungpinang Makmur Bersama to be able to analyze the right business strategy to be implemented. The data collected in this study came from two sources: The primary data collection method was carried out by direct interviews with informants. The informants in this study are the management of PT. Tanjungpinang Makmur Bersama. Secondary data used in this research can be in the form of documents in the format of Financial Statements, Work Plans and Company Budgets, Company Business Plans. The results of the research are presented qualitatively and quantitatively in this study, while the managerial implications and suggestions are also explained in detail at the end of this study.